KAWASAN WISATA WATERFRONT TANJUNG ADIKARTO KULON PROGO - muflihah, azizah nurul; Natalia, Dita Ayu Rani (Jurnal Arsitektur ZONASI, 2020)
Abstract: Tourism is one of the biggest sectors in Yogyakarta. The increasing number of new tourist destinations has increased the number of tourists. Increasing visitors every year makes the Yogyakarta government make a policy about tourism, one of which is the development of tourism in the coastal area of Kulon Progo. Kulon Progo Regency is one of the tourist destinations that has many natural and culinary attractions. Downstream of the Serang river which is next to Tanjung Adikarto port in Karangwuni village, Wates has the potential as a tourist area with high natural resources and potential fish. The development of this area aims to empower the surrounding community with the main livelihood of the population are fishermen and traders. However, the surrounding community is less able to utilize its natural resources. Then the need for encouragement from the development of this region with the concept of community development. This approach aims to accommodate the economic needs of fishermen by designing fishing areas specifically for small fishermen on the Serang river and the food court used to process fish caught by fishermen to have a higher selling value. Support local traders and industries in Kulon Progo by designing souvenir centers so that local products can be marketed. This concept aims to increase the social status and economic status of the community. And can reduce the unemployment rate which is still quite high in Kulon Progo.Keywords: community development; TanjungAdikarto; waterfront tourism.Abstrak: Pariwisata merupakan salah satu sektor terbesar di Yogyakarta. Semakin banyaknya destinasi wisata baru membuat peningkatan jumlah wisatawan. Bertambahnya pengunjung setiap tahunnya membuat pemerintah Yogyakarta membuat kebijakan tentang pariwisata, salah satunya adalah pengembangan pariwisata di kawasan pesisir pantai Kulon Progo. Kabupaten Kulon Progo merupakan salah satu destinasi wisata yang memiliki banyak tempat wisata alam dan kuliner. Hilir sungai Serang yang berada disamping pelabuhan Tanjung Adikarto di desa Karangwuni, Wates memiliki potensi sebagai kawasan wisata dengan sumber daya alam dan potensi ikan yang cukup tinggi. Pembangunan kawasan ini bertujuan untuk memberdayakan masyarakat sekitar dengan mata pencaharian utama penduduk adalah nelayan dan pedagang. Namun masyarakat sekitar kurang mampu memanfaatkan sumber daya alam yang dimilikinya. Maka perlu adanya dorongan dari pembangunan kawasan ini dengan konsep community development. Pendekatan ini bertujuan untuk mewadahi kebutuhan perekonomian nelayan dengan merancang area pemancingan khusus nelayan kecil di sungai Serang dan foodcourt yang digunakan untuk mengolah ikan hasil tangkapan nelayan agar memiliki nilai jual lebih tinggi. Mendukung pedagang dan industri lokal yang terdapat di Kulon Progo dengan merancang pusat oleh-oleh sehingga produk lokal bisa dipasarkan. Konsep ini bertujuan untuk menaikkan status sosial dan status ekonomi masyarakat. Serta dapat mengurangi tingkat pengangguran yang masih cukup tinggi di Kulon Progo.Kata Kunci: community development; Tanjung Adikarto; wisata waterfront.